2009
DOI: 10.1577/m08-129.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Chinook Salmon Bag Limits on Alewife Abundance: Implications for Lake Michigan Management Goals

Abstract: To predict effects of modifying the daily bag limit (DBL) on management of Chinook salmon Oncorhynchus tshawytscha and alewives Alosa pseudoharengus, we analyzed harvest and effort data collected from both charter and noncharter anglers during 1997–2005 in Michigan waters of Lake Michigan. Overall, the percent of anglers who caught the DBL of three Chinook salmon was low for charter (10.2%) and noncharter (3.3%) angler groups. However, during 1997–2005, the percent of anglers that caught their DBL increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, the recruitment model does not provide management guidance detailing social, economic or political guidance regarding yellow perch or other recreational or commercial fishes. For example, although an alewife reduction in Lake Michigan may benefit yellow perch recruitment, this reduction would potentially alter recreational catch of salmonids (Claramunt et al. 2009) and impair Chinook salmon, Oncorhynchus tshawytscha (Walbaum) (Holey et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recruitment model does not provide management guidance detailing social, economic or political guidance regarding yellow perch or other recreational or commercial fishes. For example, although an alewife reduction in Lake Michigan may benefit yellow perch recruitment, this reduction would potentially alter recreational catch of salmonids (Claramunt et al. 2009) and impair Chinook salmon, Oncorhynchus tshawytscha (Walbaum) (Holey et al.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that the negative binomial is often a reasonable probability distribution for analyzing catch data because these data often exhibit over-dispersion (Claramunt et al, 2009;Clark, 1974;Power and Moser, 1999;Pradhan and Leung, 2006;Ward and Myers, 2005). Additionally, preliminary analysis that also involved testing the Poisson and geometric distributions indicated that assuming the negative binomial probability distribution provided the best fit to the observed data.…”
Section: Discussionmentioning
confidence: 99%
“…Dettmers et al (2012) state that "…fishery management agencies have collaboratively developed an indicator-based decision model …" (p. 497) but fail to provide citations for this management approach or for the science underlying this approach (see, for example, Claramunt et al 2008Claramunt et al , 2009Claramunt et al , 2012. They also fail to acknowledge the fact that the approach has been shared and adopted, in part or fully, across management jurisdictions and lakes; for example, this approach received recognition from the American Fisheries Society Fisheries Administrators Section as the Outstanding Sport Fish Restoration Project in 2005.…”
Section: The Perspectivementioning
confidence: 99%